Exploring the collateral impact of the COVID-19 pandemic on communication:: Displaying affect in email discourse - Alvanoudi, Angeliki; Desilla, Louisa (Aegean Working Papers in Ethnographic Linguistics, 2022)
The present study explores how the COVID-19 pandemic has shaped the linguistic patterns found in computed-mediated discourse, drawing on a corpus of emails written by university students and addressing their lecturers. The analysis shows that affect is a key component of the new stylistic practice that has emerged in email discourse during the pandemic and reveals the ways in which manifestations of empathy are linked to politeness strategies. The first part of the analysis targets lexical and grammatical features/structures that refer to the pandemic and well-being and display affect in email discourse, and it establishes a link between this stylistic practice and dominant public discourses about the pandemic. The second part of the analysis zooms in on a particular aspect of affect, i.e., empathy, and examines pertinent politeness strategies used by students. Moreover, an attempt is made to shed some light on the potential interplay between empathy, vulnerability, and politeness.